Hubungan Modal Sendiri dan Total Asset Terhadap Sisa Hasil Usaha Di KSPPS BMT Mandiri Sejahtera Jatim - Wahyunita Putri, Indri; Fahrullah (Jurnal Ekonomika dan Bisnis Islam, 2020)
This study aims to determine the relationship between own capital and total assets with the remaining operations at KSPPS BMT Mandiri Sejahtera Jawa Timur Kantor Pusat Karangcangkring Dukun Gresik. This research uses an associative quantitative approach and the analysis technique used is multiple correlation analysis. The data source used is secondary data with financial statements and the results of the Annual Member Meeting (RAT) in 2004-2018 which was processed using SPSS version 23. The results of this study indicate that own capital and total assets have a strong relationship with the remaining operation at KSPPS BMT Mandiri Sejahtera Jawa Timur Kantor Pusat Karangcangkring Dukun Gresik. The results of the coefficient of determination (R2) show that the variable of equity and total assets have a relationship of 76,5% with the residual variable of operating results.